Five wishes how answering one simple question can make your dreams come true - Hendricks, Gay; New World Library (Novato, CA. : New World Library, 2008)
Gay Hendricks had an extraordinary, life-altering experience during a conversation at a party. The gift he received in that meeting became his touchstone for creating the life of his dreams. Now he passes on to all of us the pivotal insight he gained in that magic moment
Title from container
Keywords: Success; Goal (Psychology); Self-actualization (Psychology); Life